Aplicação do Team-Based Learning (TBL) modificado na modalidade presencial versus remota com estudantes de medicina: análise comparativa dos métodos - Teixeira, Anderson Alexsander Rodrigues (2023)
Teaching is a dynamic process, and it is believed that the best way to ensure the success of the teaching-learning relationship is to make the student the protagonist of the process. In this context, the main role of the teacher is to encourage, guide, and provide learning situations. Team-Based Learning (TBL) is an active teaching methodology. In this teaching methodology, students must study the subject in advance, and on the day of the activity, a questionnaire is administered individually, and then in pre-established groups. In this study, learning and perception of the methodology were comparatively evaluated by students from The Medical School of the Federal University of Ceará (Universidade Federal do Ceará – UFC) - Fortaleza Campus using the TBL method modified in face-to-face and remote teaching modalities, The proposed modifications included appointing group leaders and creating WhatsApp groups for discussion topics. Demographic, educational, previous experience with active methodologies, and personality profile data were collected. Students were randomly assigned to face-to-face and remote groups based on data such as gender, age, and personality test. In each class, pre and post-tests were conducted, and at the end of the course, participants evaluated their perception of the methodology. Thirty-three students participated in the study, with a median age of 20.5 years, and 64% were male. In the comparative analysis between pre-tests and posttests, a significant difference was observed in all subjects covered, regardless of the teaching modality (p < 0.001), indicating that TBL is an effective methodology. There was no difference in averages when comparing remote and face-to-face groups. In the internal consistency analysis based on the questionnaire addressing students' perceptions, most questions showed good consistency with a total correlation coefficient and Cronbach's alpha close to 1. The answers indicated a good acceptance of the methods among students and emphasized the importance of conducting pre-tests before activities, as well as creating communication groups (WhatsApp) and appointing leaders. The results suggest that modified remote TBL is effective in facilitating the teaching-learning process and it is accepted by medical students similar to face-to-face TBL.